Effectiveness of Space Maintainers in Pediatric Patients: A Systematic Review and Meta-Analysis - MDolores Casaña-Ruiz; Juan Ignacio Aura-Tormos; Laura Marques-Martinez; Esther Garcia-Miralles; Marcelino Perez-Bermejo (Dentistry Journal)
Background: Evaluating the effectiveness and survival rates of space maintainers is crucial for optimal pediatric dental care. The present study’s goal is to evaluate the survival rate of different types of space maintainers—removable, fixed with a metal base, or fixed with a resin base—indicated for children as a consequence of premature loss of primary teeth. Methods: A systematic review was conducted in accordance with PRISMA recommendations and was previously registered in PROSPERO under registration number: CRD42024534183. The search was performed in five different databases PubMed, EMBASE, Scopus, Cochrane, and Web of Science. This was supplemented by a manual database search. From the initial electronic search of the five databases, 72 articles were identified after removing duplicates. After reading the titles and abstracts, 46 articles were excluded, leaving a total of 26 studies. Upon reading the full texts, 15 were excluded for not meeting the inclusion criteria, resulting in a total of 11 articles included in the systematic review. Results: The total number of patients treated in the studies was 479, with four observational studies and seven randomized clinical trials. Fixed space maintainers, such as band and loop (BL) or lingual arch (LA), are preferred due to their long-term stability and lower risk of loss. In contrast, removable maintainers, such as Hawley plates, are suitable temporarily but require more patient cooperation and may be less tolerated. Conclusions: Space maintainers help prevent the migration of adjacent teeth and the need for more invasive orthodontic treatments in the future. Additionally, they contribute to adequate masticatory function and speech development.